Aktivace specifických místních zdrojů v ekonomickém rozvoji Moravskotřebovska - Jakubšová, Barbora (Univerzita Pardubice, 2006)
Diplomová práce se zaměřuje na problematiku aktivace specifických místních zdrojů, konkrétně v mikroregionu Moravskotřebovsko-Jevíčsko. Je zde vysvětleno, co jsou specifické místní zdroje, jaké jsou jejich vlastnosti, jak se uplatňují v místním rozvoji a jaké jsou druhy politik, které je využívají. V poslední kapitole jsou již konkrétně analyzovány a ohodnoceny jednotlivé možnosti aktivace specifických místních zdrojů na Moravskotřebovsku-Jevíčsku, které by měly vést k ekonomickému rozvoji tohoto mikroregionu.

The thesis is focused on questions of activation of rural amenities, concretely in Moravskotřebovsko-Jevíčsko region. Kinds of amenities, their characteristics and the way we can use them in local development and what kinds of politics making use of amenities exist is described here. In the last part individual options of rural amenities activation in Moravskotřebovsko-Jevíčsko region that should end in economical development of this region are explained in detail.
Activation of rural amenities in economical development of Moravská Třebová region
Keywords: rural amenities; Regional development; místní zdroje; Regionální rozvoj; Moravskotřebovsko-Jevíčsko